Synthesis, microstructure and properties of Ti(C, N)-(HfZrTaNbTi)C5-HEA high-entropy cermets by high-energy ball milling and spark plasma sintering. Issue 20 (15th October 2022) - Li, Zhanjiang; Chen, Li; Chang, Fa; Hong, Chunfu; Zhao, Xianrui; Fang, Yihang; Dai, Pinqiang
Abstract: High-entropy carbide ceramics have received extensive attention because of their excellent mechanical properties and better oxidation resistance. However, the additive phase of Ti(C, N)-based cermets has not been reported yet. In this study, (HfZrTaNbTi)C5 high-entropy ceramics (HECs) with equal atomic ratios were successfully prepared by high-energy ball milling. The results show that the HECs possess a single-phase cubic rock salt structure, fine grains, and a uniform element distribution. Then, it was used as the additive phase of Ti(C, N)-based cermets. And with AlCoCrFeNi2.1 high-entropy alloy (HEA) as binder, Ti(C, N)-HECs-HEA high-entropy cermet block materials was successfully prepared by SPS technology. The room temperature mechanical properties and high-temperature oxidation properties of high-entropy cermets have been studied. The results show that unlike traditional Ti(C, N)-based cermets, the hard phase of high-entropy cermets is composed of black core-white inner ring-grey outer ring grains and grey grains. The grey contrast phase is the newly formed (HfZrNbTaTi)(C, N) high-entropy ceramic phase. Compared with traditional Ti(C, N)-based cermets, high-entropy cermets not only have a considerable hardness (1780.3 HV) but also have relatively higher Vickers indentation fracture toughness (9.22 MPa m 1/2 ) and bending strength (1315 MPa). After being oxidized in air at 1000 °C for 60 min, the high-entropy cermets shows excellent oxidation resistance, with a dense oxide layer and fine oxide particles. The continuous and dense oxide layer effectively prevents the transport of oxygen into the cermets matrix. And the lattice distortion effect and slow diffusion effect of high-entropy alloys and high-entropy ceramics retard the diffusion of elements.